TAKAFUL AGENT MUST FOSTER PUBLIC UNDERSTANDING OF TAKAFUL - Muhammad Adi Zhafri Ahmad Samsuri; Jasri Jamal (Fakultas Hukum, Universitas Diponegoro, 2017)
The Takaful industries need agents to market the Takaful products to the public. Takaful agents play a great role in current marketing practice for Takaful distribution. Besides representing their operators and products, the agents would present this Takaful as an Islamic Insurance. The agents need to foster public understanding of Takaful instead of Conventional Insurance. To achieve this, all of the values as stated in the Al-Quran and practice through the Sunnah will be implemented by the Takaful agents to realize the objective of Takaful as an Islamic alternative for conventional Insurance. Of course this can be an option for the public to choose either one, but still, as Muslim people, we should support Takaful for Muslim sake.